Resolution of dopamine and serotonin receptor components of [3H]spiperone binding to rat brain regions. - List, S J (1981)
A procedure was developed to identify receptors for dopamine and serotonin separately and selectively by means of [3H]spiperone and to measure the density of each receptor in different regions of the rat brain. In the striatum, the binding of [3H]spiperone to dopamine receptors was inhibited by sulpiride but not by quinazolinedone R43448 (R43448); in the frontal cortex, however, the binding of [3H]spiperone to serotonin receptors was inhibited by R43448 but not by sulpiride. Thus, the density of dopamine receptors (D2 sites) was measured by [3H]spiperone binding in the presence of 0.1 microM R43448 (to preclude the attachment of the 3H-labeled ligand to serotonin sites), while the density of serotonin receptors (S2 sites) was measured by [3H]spiperone binding in the presence of 10 microM sulpiride (to preclude the attachment of the 3H-labeled ligand to dopamine sites). The density of D2 sites was highest in the striatum, followed by the olfactory tubercle, hypothalamus, substantia nigra, and the lower pons--medulla region. All five regions had similar dissociation constants (Kd values) of 0.05--0.15 nM. The density of S2 sites was highest in the frontal cortex, followed by the posterior cortex, olfactory tubercle, striatum, hypothalamus, and thalamus, and all regions had Kd values in the range 0.6--2.3 nM. Thus, because the Kd values were similar for all regions, and because Scatchard analyses revealed a single set of sites for either D2 or S2 (where detected), the main criteria for resolving the dopamine and serotonin components of [3H]spiperone binding were considered fulfilled.